CONFIRMATION OF THE PRESENCE OF THE SPECIES CIXIDIA PILATOI (D'URSO & GUGLIELMINO, 1995) (FULGOROMORPHA: ACHILIDAE) IN THE REPUBLIC OF MOLDOVA - Grozdeva, Svetlana (CEP USM, 2023)
This paper presents the information about the species Cixidia pilatoi (D'Urso & Guglielmino, 1995), that was detected in Brînzeni commune, Edineț district in 2021-2022. It was described at the first time in 1995 from the Italian peninsula. Another species of this genus, Cixidia marginicollis (Spinola, 1839), was previously indicated for the cicada fauna of the Republic of Moldova. After a revision made in 1995, the authors D'Urso & Guglielmino revealed that C. marginicollis is spred only in Sicily, while the statementes made before that year may be related to the species C. pilatoi.
GROZDEVA, Svetlana. Confirmation of the presence of the species cixidia pilatoi (d'urso & guglielmino, 1995) (fulgoromorpha: achilidae) in the Republic of Moldova. In: Plant Protection - Achievements and Perspectives: scientific international symposium, Chisinau, October 2-3, 2023. CEP USM, 2023. pp.45-50. ISBN 978-9975-62-563-0. DOI:https://doi.org/10.53040/ppap2023.07.
Keywords: cicada; Cixidia pilatoi; description; biology; ecology